Augmented and Virtual Realities: the Future of Building Design and Visualization - Solanki, Divyarajsinh M.; Laddha, Hrushikesh; Kangda, Muhammed Zain; Noroozinejad Farsangi, Ehsan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The present study precisely conveys the methodology of developing a three-dimensional (3D) architectural model of a villa with its walk-through and displaying the model in virtual reality, which as a result, be used by the clients to spectate, customize and buy the real estate property.
Keywords: CE-Pedagogy (CE: Civil Engineering); modeling; Augmented Reality; virtual reality; real-estate; simulation